Application of a Line Laser Scanner for Bed Form Tracking in a Laboratory Flume. Issue 3 (23rd March 2018) - de Ruijsscher, T. V.; Hoitink, A. J. F.; Dinnissen, S.; Vermeulen, B.; Hazenberg, P.
Abstract: A new measurement method for continuous detection of bed forms in movable bed laboratory experiments is presented and tested. The device consists of a line laser coupled to a 3‐D camera, which makes use of triangulation. This allows to measure bed forms during morphodynamic experiments, without removing the water from the flume. A correction is applied for the effect of laser refraction at the air‐water interface. We conclude that the absolute measurement error increases with increasing flow velocity, its standard deviation increases with water depth and flow velocity, and the percentage of missing values increases with water depth. Although 71% of the data is lost in a pilot moving bed experiment with sand, still high agreement between flowing water and dry bed measurements is found when a robust LOcally weighted regrESSion (LOESS) procedure is applied. This is promising for bed form tracking applications in laboratory experiments, especially when lightweight sediments like polystyrene are used, which require smaller flow velocities to achieve dynamic similarity to the prototype. This is confirmed in a moving bed experiment with polystyrene. Key Points: A new line laser scanner approach improves bed level monitoring in morphodynamic experiments A LOESS fitting algorithm allows to handle outliers and missing data effectively The best results are obtained for small flow velocities commonly used in experiments with light‐weight sediment